Collaborative cloud IDS in detecting denial of service by dendritic cell mechanism - Ahmad, Azuan; Kama, Mohd Nazri; Azmi, Azri; Idris, Norbik Bashah (International Journal of Electrical and Electronic Engineering & Telecommunications, 2019)
The term Cloud computing is not new in computing technology. This form of computing technology previously considered only as marketing term, but today Cloud computing not only provides innovative improvements in resource utilisation but it also creates a new opportunity in data protection mechanisms where the advancement of intrusion detection technologies are blooming rapidly. From the perspective of security, Cloud computing also introduces concerns about data protection and intrusion detection mechanism. This paper aims to provide a Denial of Service (DoS) detection for Cloud computing environment. As a result, we provide an experiment to examine the capability of the proposed system. The result shows that the proposed system was able to detect all types of attacks that conducted during the experiment. We conclude the paper with a discussion on the results, then we include together with a graphical summary of the experiment's result.